Anglo-Jewry since 1066 : place, locality and memory - Kushner, Tony (Antony Robin Jeremy) (Manchester University Press, 2009)
This history of Anglo-Jewry covers medieval, early modern and modern periods. The book puts emphasis on the construction of place identity between local, national and global identities.